Phase III study of the European Organisation for Research and Treatment of Cancer satisfaction with cancer care core questionnaire (EORTC PATSAT‐C33) and specific complementary outpatient module (EORTC OUT‐PATSAT7). (2nd November 2017) - Brédart, A.; Anota, A.; Young, T.; Tomaszewski, K.A.; Arraras, J.I.; Moura De Albuquerque Melo, H.; Schmidt, H.; Friend, E.; Bergenmar, M.; Costantini, A.; Vassiliou, V.; Hureaux, J.; et al.
Abstract : Advances in cancer care delivery require revision and further development of questionnaires assessing patients' perceived quality of care. This study pre‐tested the revised EORTC satisfaction with cancer care core questionnaire applicable in both the cancer inpatient and outpatient settings, and its new, outpatient‐specific complementary module. The process of revision, development of the extended application, and pre‐testing of these questionnaires was based on phases I to III of the "EORTC Quality of Life Group Module Development Guidelines." In phase III, patients in 11 countries in four European regions, South America and Asia completed provisional versions of the questionnaires. Fifty‐seven relevant issues selected from literature reviews and input from experts were operationalized into provisional items, and subsequently translated into ten languages. Assessment of understanding, acceptability, redundancy and relevance by patients (n = 151) from oncology inpatient wards, and outpatient chemotherapy, radiotherapy and consultation settings, led to retention of, deletion of and merging of 40, 14 and 6 items respectively. Cronbach's alpha coefficients for hypothesized questionnaire scales were above 0.80. Our results provide preliminary support for the 33‐item EORTC Satisfaction with cancer care core questionnaire and the 7‐item complementary module specific for the outpatient care setting. A large scale phase IV cross‐cultural psychometric study is now underway.